Analysis of Islamic Social Capital in Improving Welfare in MSMEs Group Financing - Sabrina Natasya Matondang; Muhammad Lathief Ilhamy Nasution; Nur Ahmadi Bi Rahmani (Journal of Applied Business Administration, 2025)
This study aims to analyze the implementation of Islamic Social Capital in improving the welfare of members of the MSMEs (Micro, Small, and Medium Enterprises) financing group under PNM Mekaar in Jaring Halus Village. The background of this research is based on the importance of Islamic values in shaping social solidarity, trust, and collective responsibility within community economic empowerment programs. This study uses a qualitative approach with a case study method, where data were collected through observation, in-depth interviews, and documentation. The results show that Islamic values such as honesty (sidq), trustworthiness (amanah), mutual assistance (ta'awun), and moral discipline have become social strengths that drive smooth financing, increased business turnover, and the emergence of collective aspirations towards a blessed and independent business. Furthermore, synergy with religious figures and social institutions strengthens the potential for sustainable business development. This study concludes that Islamic Social Capital serves not only as a moral foundation but also as an effective and applicable strategy for economic empowerment.